SMArDT modeling for automotive software testing. (26th October 2018) - Drave, Imke; Hillemacher, Steffen; Greifenberg, Timo; Kriebel, Stefan; Kusmenko, Evgeny; Markthaler, Matthias; Orth, Philipp; Salman, Karin Samira; Richenhagen, Johannes; Rumpe, Bernhard; Schulze, Christoph; von Wenckstern, Michael; et al.
Summary: Efficient testing is a crucial prerequisite to engineer reliable automotive software successfully. However, manually deriving test cases from ambiguous textual requirements is costly and error‐prone. Model‐based software engineering captures requirements in structured, comprehensible, and formal models, which enables early consistency checking and verification. Moreover, these models serve as an indispensable basis for automated test case derivation. To facilitate automated test case derivation for automotive software engineering, we conducted a survey with testing experts of the BMW Group and conceived a method to extend the BMW Group's specification method for requirements, design, and test methodology by model‐based test case derivation. Our method is realized for a variant of systems modeling language activity diagrams tailored toward testing automotive software and a model transformation to derive executable test cases. Hereby, we can address many of the surveyed practitioners' challenges and ultimately facilitate quality assurance for automotive software.